2005
DOI: 10.1590/s1678-91992005000400014
|View full text |Cite
|
Sign up to set email alerts
|

Renal involvement in visceral leishmaniasis dogs

Abstract: Visceral leishmaniasis (VL) is a zoonosis that affects both animals and man. Dogs are the etiological agent's main reservoir. The aim of this study was to evaluate the clinical laboratory aspects and renal histopathology of VL dogs. Thirtyfour symptomatic (case) and 17 asymptomatic (control) VL seropositive dogs of different breeds, sexes, and ages from Teresina, Piauí State, Brazil, were used. Diagnosis was confirmed by enzyme-linked immunosorbent assay and indirect immunofluorescence test. Clinical and labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(9 reference statements)
0
1
0
1
Order By: Relevance
“…Canine visceral leishmaniasis is thought to be an immune-mediated disease; where the presence of a humoral response is associated with clinical disease, while the cellular response has been observed in asymptomatic animals 1,17 . A study of dog kidney fragments showed significant differences between membranoproliferative glomerulonephritis and the presence or absence of symptoms 24 . In the present study there was no significant difference between the presence of glomerulonephritis in symptomatic and oligosymptomatic groups, assuming that the renal alterations are more related to immune status and immune cell response of dogs than to the presence of signs and symptoms and exposure time 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Canine visceral leishmaniasis is thought to be an immune-mediated disease; where the presence of a humoral response is associated with clinical disease, while the cellular response has been observed in asymptomatic animals 1,17 . A study of dog kidney fragments showed significant differences between membranoproliferative glomerulonephritis and the presence or absence of symptoms 24 . In the present study there was no significant difference between the presence of glomerulonephritis in symptomatic and oligosymptomatic groups, assuming that the renal alterations are more related to immune status and immune cell response of dogs than to the presence of signs and symptoms and exposure time 1 .…”
Section: Discussionmentioning
confidence: 99%
“…A perda seletiva da albumina também pode ocorrer pela urina em decorrência à lesão renal (Grauer, 2005). A frequente proteinúria observada está relacionada à doença glomerular e é reflexo do aumento da permeabilidade capilar glomerular a proteínas do plasma, principalmente a albumina (Soares et al, 2005). Assim como foi observado no presente estudo onde 83,33% (5/6) dos cães positivos apresentaram presença de moderada (30 mg/dL) à marcante (100 mg/dL) de proteínas (albumina) na urina.…”
Section: Discussionunclassified
“…Visceral leishmaniasis (VL) is an infectious, systemic, and zoonotic disease caused by the protozoan Leishmania infantum and is transmitted by infected female sandfl ies, Lutzomyia longipalpis, and its main vector is in Brazil (Dantas-Torres and Brandão-Filho, 2006). It is estimated that there are millions of infected dogs in South America, especially in Brazil, where there are high rates of infection (Marcondes and Day, 2019) Infected dogs can develop canine leishmaniosis (CanL), which can aff ect several organs and therefore exhibit several clinical characteristics, ranging from apparently healthy to severe illness and death, depending on the immune response triggered by the patient (Soares et al, 2005;Freitas et al, 2012) Renal function impairment is quite frequent among the clinical changes observed in infected animals (Braga et al, 2015). Th e formation and deposition of immune complexes secondary to CanL can cause glomerulonephritis and tubulointerstitial lesions (De Oliveira Frazilio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors believe that tubulointerstitial lesions occur secondary to glomerulopathy (Pardo-Marín et al, 2017; De Oliveira Frazilio et al, 2018). Renal proteinuria, which is a refl ection of increased glomerular capillary permeability, is associated with the production of immune complexes and may be evidence of kidney injury (D' Amico and Bazzi, 2003; Soares et al, 2005;Freitas et al, 2012;Brown et al, 2013;IRIS 2023). Treatments for CanL in Brazil are based on miltefosine for leishmanicidal action, immunomodulatory medications such as domperidone, and immunotherapy, which consists of three double doses of the Leishtec® vaccine with intervals of twenty-one days between applications.…”
Section: Introductionmentioning
confidence: 99%